Bio-efficacy of Herbicides on Nutrient Uptake, Yield and Economics of Groundnut - Kowser, Tasmiya; Nagalikar, V. P.; Halepyati, A. S.; Krishnamurthy, D.; Negalur, R. B. (International Journal of Bio-resource and Stress Management, 2023)
Field experiment was conducted during July to October, kharif, 2013 on red sandy loam soil to find out efficient method of weed control in groundnut at College of Agriculture, Raichur, Karnataka, India. Results indicated that, pod yield obtained with pre and post emergent herbicides along with intercultivation at 35 Days After Sowing (DAS) were comparable with interculture at 15, 30 and 40 days after sowing+one hand weeding at 25 days after sowing and pendimethalin 38.7 CS @ 1000 g a.i. ha-1+2 IC at 25 and 35 DAS. Weed control efficiency of 61.55% was achieved in integrated method compared to 22.94% with herbicides application alone at harvest. Among the herbicides application of pendimethalin at 1000 g a.i. ha-1 fb imazethapyr at 75 g a.i. ha-1 was found superior in terms of pod yield, haulm yield and weed control efficiency. From the studies it can be concluded that significantly higher net returns (Rs. 99,518 ha-1) was recorded in weed free check followed by pendimethalin 38.7 CS 1000 g a.i. ha-1 fb imazethapyr 10 SL @ 75 g a.i. ha-1 fb IC at 35 DAS. On the other hand significantly lower net returns of (Rs. 17,768 ha-1) were registered with weedy check compared to rest of the treatments. The highest B:C (3.52) was obtained from weed free check.